Perlindungan Hukum Bagi Pencari Suaka (Asylum Seeker) Di Wilayah Indonesia - Eko Wahyudi; Miko Aditiya Suharto; Pramesti Ivana Putri Kinasih (Fakultas Hukum Universitas Muhammadiyah Sorong, 2023)
The research's main goal is to ascertain the differences between the legal protections provided to refugees and asylum seekers on Indonesian territory under international law and Indonesian national law, as well as the legal repercussions that asylum seekers will face there under international refugee law. This study employs a statutory approach and a conceptual approach in its normative juridical research methodology. The legal resources employed in this study are primary legal resources, such as laws and international conventions, and secondary legal resources, such as books and scholarly journals. In order to satisfy human rights, including the provision of legal protection and the treatment of foreign refugees and asylum seekers, the study findings are connected to Indonesian laws and regulations as well as global norms. Keywords : Asylum Seeker, Refugee, Legal Protection, UNHCR.